Pengaruh Tunjangan Kinerja dan Promosi Jabatan untuk Meningkatkan Prestasi Kerja dengan Motivasi Kerja Sebagai Variabel Intervening pada Sekretariat Daerah Kabupaten Bondowoso - Hadi, Samsul; Herlambang, Toni; Cahyono, Dwi (BUDGETING : Journal of Business, Management and Accounting, 2024)
Upon identifying issues in the responsibilities and operations of the Bondowoso Regency Regional Secretariat, it is evident that numerous activity programmes have not met the anticipated realisation targets. This suggests that the personnel of the Bondowoso Regency Regional Secretariat are not performing at their best. This research aims to directly and indirectly analyse the impact of performance allowances and job promotions on enhancing work performance, with work motivation serving as an intervening variable at the Bondowoso Regency Regional Secretariat. This study consisted of 197 samples. The analysis method employed was Structural Equation Modelling (SEM) with WarpPLS 7.0. The data analysis results indicate that the performance allowance and job promotion variables have a significant impact on work motivation and performance. Performance allowances and job promotions have a major impact on work performance by influencing work motivation as an intervening factor. Data analysis results indicate that the variables performance allowance, work motivation, and promotion have a partial significant impact on work performance at the Bondowoso Regency Regional Secretariat. Keywords: Performance Allowance, Promotion, Work Motivation And Work Performance